2013
DOI: 10.1021/jf305208e
|View full text |Cite
|
Sign up to set email alerts
|

Oil, Fatty Acid, Flavonoid, and Resveratrol Content Variability and FAD2A Functional SNP Genotypes in the U.S. Peanut Mini-Core Collection

Abstract: Peanut seeds contain high amounts of oil and protein as well as some useful bioactive phytochemicals which can contribute to human health. The U.S. peanut mini-core collection is an important genetic resource for improving seed quality and developing new cultivars. Variability of seed chemical composition within the mini-core was evaluated from freshly harvested seeds for two years. Oil, fatty acid composition, and flavonoid/resveratrol content were quantified by NMR, GC, and HPLC, respectively. Significant va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 32 publications
9
74
1
2
Order By: Relevance
“…In soybean seeds, however, the oil content is negatively correlated with protein content, and soybean isoflavone is negatively correlated with fat and positively correlated with protein content (Charron et al 2005). In the above-mentioned mini-core collection of American peanut studied by Wang et al (2013), no significant correlation between the fatty acid content and the contents of flavonoids such as quercetin and genistein was detected. In this study, we analyzed the correlation between TFC in peanut and several primary storage substances.…”
Section: Hou Et Almentioning
confidence: 92%
See 3 more Smart Citations
“…In soybean seeds, however, the oil content is negatively correlated with protein content, and soybean isoflavone is negatively correlated with fat and positively correlated with protein content (Charron et al 2005). In the above-mentioned mini-core collection of American peanut studied by Wang et al (2013), no significant correlation between the fatty acid content and the contents of flavonoids such as quercetin and genistein was detected. In this study, we analyzed the correlation between TFC in peanut and several primary storage substances.…”
Section: Hou Et Almentioning
confidence: 92%
“…Studies on peanut flavonoids, however, have so far focused on the flavonoid types found in seeds (Wang et al 2008), the variation in the range of flavonoid contents, and the relationship between flavonoid content and seed-coat color (Wang et al 2013, Chukwumah et al 2009, Yoav et al 2012). High quality is important for cultivar breeding, at the same time yield and resistant traits are also major factors in breeding research.…”
Section: Hou Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Tokuşoğlu et al (2005) studied six peanut cultivars from the local Turkish market for trans-and cisresveratrol and found mainly the trans-resveratrol compound, the level being between 0.03 and 1.92 mg/kg. Wang et al (2013b) investigated the mini-core collection of peanut material (102 accessions representing 1% of the germplasm collection) in the USA for the potential to improve seed quality through genetic resources by measuring the variability of seed chemical composition. One of the parameters investigated was resveratrol content.…”
Section: Stilbenes In Nuts and Almondsmentioning
confidence: 99%